Analysis of The Utilization of Green Open Spaces by The Community of Samarinda City - Aini, Nurul; Setyasih, Iya’ (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Green Open Spaces (GOS) in Samarinda are developed to serve ecological functions, provide recreation, include jogging tracks, serve as gathering areas, and act as river buffer zones. Several frequently visited GOS in Samarinda include Teras Samarinda, Samarendah Park, Smart Park/Edupark, and Bebaya Park. This study aims to analyze the use of GOS in Samarinda City, focusing on user characteristics, activity patterns, and factors influencing utilization levels. The research method combines a quantitative survey using questionnaires and a qualitative phenomenological approach to explore users' experiences. The sample consisted of 111 participants who utilize GOS for recreation, sports, social interaction, and other activities. The results show that the majority of activities carried out are relaxing (73.0%), walking (63.1%), and taking photos or creating content (49.5%), mostly with friends or family. The most frequently visited GOS is Samarendah Park, and the main factors affecting comfort and engagement are scenic beauty, cleanliness, and safety. Therefore, the Samarinda city government, in developing the GOS, needs to pay close attention to the community's needs.